Anatomical Mechanisms of Leaf Blade Morphogenesis in Sasaella kogasensis ‘Aureostriatus’ - Wanqi Zhao; Zhuo Lv; Hanjiao Zhang; Jiahui Yue; Xu Zhang; Long Li; Feiyi Huang; Shuyan Lin (Plants, 2024)
There are limited studies on the cytology of bamboo leaf development from primordium to maturity. This study delves into the leaf morphological characteristics and growth patterns of Sasaella kogasensis ‘Aureostriatus’ and provides a three-dimensional anatomical analysis of cell division, expansion, and degradation. Leaves on the same branch develop bottom-up, while individual leaves develop the other way around. Like bamboo shoots and culms, the leaves follow a “slow–fast–slow” growth pattern, with longitudinal growth being predominant during their development. The growth zones of individual leaves included division, elongation, and maturation zones based on the distribution of growth space. By measuring 13,303 epidermal long cells and 3293 mesophyll cells in longitudinal sections of rapidly elongating leaves, we observed that in the rapid elongation phase (S4–S5), the division zone was located in the 1–2 cm segment at the bottom of the leaf blade and maintained a constant size, continuously providing new cells for leaf elongation, whereas in the late rapid elongation phase (S6), when the length of the leaf blade was approaching that of a mature leaf, its cells at the bottom of the blade no longer divided and were replaced by the ability to elongate. Furthermore, to gain an insight into the dynamic changes in the growth of the S. kogasensis ‘Aureostriatus’ leaves in the lateral and periclinal directions, the width and thickness of 1459 epidermal and 2719 mesophyll cells were counted in the mid-cross section of leaves at different developmental stages. The results showed that during the early stages of development (S1–S3), young leaves maintained vigorous division in the lateral direction, while periplasmic division gradually expanded from the bottom to the top of the leaf blade and the number of cell layers stabilized at S4. The meristematic tissues on both sides of the leaf were still able to divide at S4 but the frequency of the division gradually decreased, while cell division and expansion occurred simultaneously between the veins. At S6, the cells at the leaf margins and between the veins were completely differentiated and the width of the leaf blade no longer expanded. These findings revealed changes in cell growth anisotropically during the leaf development of S. kogasensis ‘Aureostriatus’ and demonstrated that leaf elongation was closely related to the longitudinal expansion of epidermal cells and proliferative growth of mesophyll cells, whereas the cell division of meristematic tissues and expansion of post-divisional cells contributed to the increases in blade width and thickness. The presented framework will facilitate a further exploration of the molecular regulatory mechanisms of leaf development in S. kogasensis ‘Aureostriatus’ and provide relevant information for developmental and taxonomic studies of bamboo plants.